Deprotection of peracetylated methyl D-ribosides through enzymatic alcoholysis: Different recognition of the anomers - Iñigo, Sabrina (2005)
The anomers methyl 2,3,5-tri-O-acetyl-α-d-ribofuranoside and methyl 2,3,5-tri-O-acetyl-β-d-ribofuranoside showed a different behaviour in the Candida antarctica B lipase-catalysed alcoholysis. While the enzymatic deprotection of the former proceeded regioselectively affording methyl 2,3-di-O-acetyl-α-d-ribofuranoside in 81% yield in 3 h at 45°C showing no further transformation, the alcoholysis of the β-diasteromer was less selective. For this anomer, mixtures of partially acetylated products were formed, but contrasting to the α epimer, full deacetylated methyl β-d-ribofuranoside was quantitatively formed at long reaction times (5 days).